Beekeeping and Honey Bee Biology History of Beekeeping in Indonesia - Minarti, Sri; Puspita, Poppy Satya (Advanced Research in Biological Science Vol. 6, 2023)
Beekeeping is an agro-based activity which is being undertaken by farmers/landless labours in rural area as an integrated farming practice. Beekeeping supplements income & employment generation and nutritional intake of rural population. Though the honeybees are best known for the honey they produce, their economic role in nature is to pollinate hundreds and thousands of flowering plants and assure setting of seed or fruit. Honeybees have been offering services to the society through ensured pollination in cross-pollinated crops as well as by providing honey and a variety of beehive products.